Penerapan Metode Latihan (Exercise) pada Pembelajaran Kitab Durusullughah Al Arabiyyah Jilid I Untuk Meningkatkan Penguasaan Mufradat Bahasa Arab Kelas VII E MTs Ngruki Sukoharjo 2023/2024 - Muza Safaanatul Khimdati Amna (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2023)
The background of this study is that the seventh-grade E (VII E) female students feel bored and inactive in Arabic language learning using the Direct Method. Additionally, 45% of the students in class VII E do not meet the Arabic language minimum passing grade (KKM). The research questions are: How is the implementation of the exercise method? What are the learning outcomes of students using the exercise method? What are the supporting and inhibiting factors in applying the exercise method? The purpose of this research is: To understand the implementation of the exercise method in Arabic language learning using Durusullughah Al-‘Arabiyyah Book I, To find out the learning outcomes of the VII E students, To identify the supporting and inhibiting factors in applying the exercise method. The research method used is a descriptive qualitative method. Data collection techniques included non-participant observation, unstructured interviews with the Arabic teacher of Durusullughah Al-‘Arabiyyah Book I and several VII E students at MTs Ngruki Sukoharjo, and documentation studies consisting of images and some conversation excerpts related to the research. Data analysis was conducted using qualitative data analysis through data reduction, data presentation, and drawing conclusions. The results of the study show that the exercise method is suitable for improving student learning outcomes, particularly in mastering Arabic vocabulary (mufradat) using Durusullughah Al-‘Arabiyyah Book I. Specifically, 20 out of 25 students were enthusiastic and active, achieving evaluation scores above the KKM (80%). Student learning outcomes improved from 55% under the Direct Method to 80% using the Exercise Method. The supporting factors in applying the Exercise Method were discipline, the teacher’s mastery of the material, and student attention. The inhibiting factors were limited class time and a noisy classroom atmosphere.